Indigenous Herbal Wellness: A Potent Threshold towards Growth of Tourism Business in Kashmir Horizon, India: Indigenous Herbal Wellness: A Potent Threshold towards Growth of Tourism Business - Badam, Tahmeed; Dar, Shahnawaz Ahmad (Turizam, 2025)
The vale is privileged with diverse floral biodiversity and would be considered an incredible potential for the growth and development of herbal wellness tourism in the region. In this perspective an investigation has been carried out to bring forth untapped treasure of bio-herbal heritage on the arena of tourism sector. The endeavor is being prompted; 1] to study potentiality of indigenous bio-herbal heritage from the perspective of wellness Tourism in Kashmir; 2] to highlight traditional medical significance of herbs in association to various ailments; 3] to discuss economic benefits of indigenous medicinal plants in light of herbal wellness tourism industry on the host community. The data was evaluated with execution of One-Way ANOVA through the pooled interval plot to point out variance (StDev) among identified contents. Further, to scrutinize current trends and prospective growth of tourist arrivals the Regression Technique has been employed along ‘fitted line plot’ to analyze data.